Diagnóstico ambiental e avaliação da capacidade de suporte das praias do bairro de Itapoã, Salvador, Bahia / Environmental diagnosis and capacity analyzes of Itapoã’s neighborhood, Salvador, Bahia - Dra. Iracema Reimão Silva; José Rodrigues de Souza Filho; Merissa Andrade Leite Barbosa; Fádia Rebouças; Ricardo Augusto Souza Machado (Sociedade & Natureza)
Itapoã’s neighborhood is best known for its natural resources and enormous cultural value. It representsthe city symbol, its unique features differentiates it from others neighborhoods. Due to its diverseattractions, in the past century, Itapoã was the most popular summer resort. But in the past decades,due to accelerated urbanization process, it became a place with overcrowded beach, high levels ofpollution and destruction of native vegetation. In this context, this article intends to analyze the capacityof support and accommodation of regular attendants of Itapoã’s beach, giving subsidizes to itsenvironmental and social management. Itapoã’s beach was divided in 55 equal units of 30 meterslength. The numbers of person occupying each area was used to calculate the area at disposition foreach user. The major parts of this neighborhood area showed an intense density, living 4 to 10 meterssquare per user. This area per person represents the minimum area tolerated by the users. During theinterviews, the dirt and lack of structures from the beach establishments were the worst problems pointedout, while the easy access and peace were the most attractive.